2002
DOI: 10.1097/00126334-200212150-00007
|View full text |Cite
|
Sign up to set email alerts
|

HIV Type 1 Group M Clades Infecting Subjects From Rural Villages in Equatorial Rain Forests of Cameroon

Abstract: Though the HIV-1 subtypes infecting patients living in urban and semi-urban areas in Cameroon have been reported, information on the subtypes infecting patients in rural villages is lacking. To begin to understand the diversity of the HIV-1 group M subtypes infecting persons living in rural villages in the equatorial rain forest regions of Cameroon, 49 plasma samples from 14 rural villages in four provinces of Cameroon were analyzed using heteroduplex mobility analysis (HMA), DNA sequencing, and phylogenetic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…Cameroon is a country in West Central Africa that harbors a broad HIV-1 genetic diversity, including all HIV-1 groups (M, N, and O), all group M (sub-) subtypes, many CRFs, and a wide variety of ISRs, as reported previously Zhong et al, 2002Zhong et al, , 2003aBurda et al, 2004; and others [Nkengasong et al, 1994;Fonjungo et al, 2000;Heyndrickx et al, 2000;Morison et al, 2001]. Initial analysis of HIV-1 subtypes in the urban and semi-urban regions of Cameroon in the mid-1990s revealed the presence of diverse subtypes at different frequencies with subtype A accounting for 60%-65% of the infections [Nkengasong et al, 1994;Heyndrickx et al, 2000].…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Cameroon is a country in West Central Africa that harbors a broad HIV-1 genetic diversity, including all HIV-1 groups (M, N, and O), all group M (sub-) subtypes, many CRFs, and a wide variety of ISRs, as reported previously Zhong et al, 2002Zhong et al, , 2003aBurda et al, 2004; and others [Nkengasong et al, 1994;Fonjungo et al, 2000;Heyndrickx et al, 2000;Morison et al, 2001]. Initial analysis of HIV-1 subtypes in the urban and semi-urban regions of Cameroon in the mid-1990s revealed the presence of diverse subtypes at different frequencies with subtype A accounting for 60%-65% of the infections [Nkengasong et al, 1994;Heyndrickx et al, 2000].…”
Section: Introductionmentioning
confidence: 64%
“…Our most recent molecular epidemiological studies in Cameroon in the years 2000-2003 show a continued predominance of CRF02_AG but also reveal the abundance of other recombinant strains. For example, sequence analysis of the pro gene of isolates obtained in the rural areas of Cameroon revealed that 60% were CRF02_AG , and additional analysis of several of these isolates in the gag and env genes showed that two-thirds were recombinants, of which almost half were CRF02_AG variants [Zhong et al, 2002[Zhong et al, , 2003a. Recombination between the predominant CRF02_AG and other HIV-1 subtypes in Cameroon eventually resulted in several CRF02_AG-containing ISRs [Zhong et al, 2002[Zhong et al, , 2003a including CRF09_cpx, which was identified recently in the town of Bamenda [Burda et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…RNA extraction was performed on 100 l of plasma as described by Boom et al (4), followed by a single-tube reverse transcriptase (RT)-PCR (Access RT-PCR system, Promega, Madison, WI) to amplify the C2V5 region of env (40). The amplified products were sequenced and phylogenetically analyzed with reference subtype sequences to determine the virus subtypes as previously described (10,41).…”
Section: Methodsmentioning
confidence: 99%
“…Human MAb 2182 was derived from a clade A virus-infected immigrant from China who is currently living in New York City (15), and MAbs 2557 and 2558 were produced from individuals who were infected with the CRF02AG virus subtype and are living in Cameroon. The clade A and CRF02AG env genes were identified by using a heteroduplex mobility assay and by sequencing, respectively (56). The irrelevant human MAb 1418 against parvovirus B19 was used as a negative control (10).…”
Section: Methodsmentioning
confidence: 99%